2007
DOI: 10.2527/jas.2006-067
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary selenium sources on growth and carcass characteristics of growing-finishing pigs fed diets containing high endogenous selenium

Abstract: A study was conducted to determine the efficacy of organic (Se-yeast, SelenoSource AF, Diamond V Mills Inc., Cedar Rapids, IA) and inorganic sources of Se on growth performance, tissue Se accretion, and carcass characteristics of growing-finishing pigs fed diets with high endogenous Se content. A total of 180 pigs at 34.4 +/- 0.06 kg of BW were allotted to 1 of 5 dietary treatments: a negative control without added Se (NC); 3 treatment diets with 0.1, 0.2, or 0.3 mg/kg of added Se from an organic source; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 25 publications
11
53
1
6
Order By: Relevance
“…Pan et al (2007) reported that tissue total Se concentrations were similar in liver tissue of laying fowl when comparing sources but greater in the muscle tissue of SY-supplemented birds when compared with SS. Similar effects of Se source have been reported within the cardiac and skeletal muscles of cattle, sheep (Juniper et al, 2008a and and loin tissue of pigs (Mahan et al, 1999;Mateo et al, 2007), whereby tissue total Se concentrations have been greater in SY-supplemented animals when compared with those receiving a comparable dose of SS.…”
Section: Selenium Content In Tissuessupporting
confidence: 68%
“…Pan et al (2007) reported that tissue total Se concentrations were similar in liver tissue of laying fowl when comparing sources but greater in the muscle tissue of SY-supplemented birds when compared with SS. Similar effects of Se source have been reported within the cardiac and skeletal muscles of cattle, sheep (Juniper et al, 2008a and and loin tissue of pigs (Mahan et al, 1999;Mateo et al, 2007), whereby tissue total Se concentrations have been greater in SY-supplemented animals when compared with those receiving a comparable dose of SS.…”
Section: Selenium Content In Tissuessupporting
confidence: 68%
“…These results were consistent with previous reports . Mateo et al (2007) reported that the drip loss of loins in 48 h in growing-finishing pigs was reduced only by SY supplementation not by SS supplementation. Zhan et al (2007) found out that SeMet was more effective in decreasing the drip loss of loin muscle than SS in finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suppose that the function of Se to improve the meat quality is through enhancing its antioxidant ability to protect against deteriorative reactions during lipid peroxidation. However, Mateo et al (2007) reported that the muscle colour of pigs was not improved by dietary Se (SY or SS) supplementation. These inconsistent results might be due to different Se sources and animals used.…”
mentioning
confidence: 99%
“…Mateo et al (2007) and Svoboda et al (2009) found no significant differences in color characteristics with selenium supplementation on the meat loin muscle tissue of Camborough x PIC boar and on the biceps femoris muscle of Landrace x Czech Large White crossbreeds. However, Mahan et al (1999) observed linear response to applied doses of selenium in the diet of an unspecified breed of pigs, when measuring lightness (L* color component), with L* increasing with the selenium dose.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, in those previous studies, the analyzed material was meat, whereas in the present work it was smoked pork loin. Meat products are characterized by different quality features than those of meat, even when the same cut is used, as observed for loin in the studies of Mahan et al (1999) and Mateo et al (2007). According to other authors (Poovey et al, 2007), the lack of influence of selenium supplementation on meat color could be associated with time and temperature conditions after slaughter, which might not allow oxidation to influence the color.…”
Section: Resultsmentioning
confidence: 98%